2006
DOI: 10.1542/peds.2005-2310
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Outcome at 3 Years of Age in Very Preterm Infants: The EPIPAGE Study

Abstract: Very preterm children have a higher risk of behavioral problems at 3 years of age compared with term-born children. Health and neurodevelopmental status of the child were significantly associated with behavioral difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
109
2
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(129 citation statements)
references
References 43 publications
10
109
2
8
Order By: Relevance
“…The EPIPAGE study (19) investigated behavioral problems in preterm children. They found that at 3 years of age these children are more likely to have behavioral difficulties (problems with peers, behavioral problems, and hyperactivity) than full-term children, even after controlling for the influence of demographic characteristics and neonatal complications.…”
Section: Personal and Social Development Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The EPIPAGE study (19) investigated behavioral problems in preterm children. They found that at 3 years of age these children are more likely to have behavioral difficulties (problems with peers, behavioral problems, and hyperactivity) than full-term children, even after controlling for the influence of demographic characteristics and neonatal complications.…”
Section: Personal and Social Development Studiesmentioning
confidence: 99%
“…Since the 1990s, improvements in perinatal and neonatal care units have led to increased survival rates (from 5% to 10%) even when the gestational age at birth is younger (18,19). Thus, in the last decade there has been a striking increase in investigations into how birth weight and gestational age influence psycho-neurological development.…”
Section: Introductionmentioning
confidence: 99%
“…A global indicator of behavioral difficulties was obtained by adding the first 4 scores. 11 The cutoff points were defined such that approximately 10% of children born at term were considered to be at risk for behavioral problems.…”
Section: E30mentioning
confidence: 99%
“…A global indicator of behavioral difficulties was obtained by adding the first 4 scores. 11 The cutoff points were defined such that approximately 10% of children born at term were considered to be at risk for behavioral problems.The propensity-score (PS) method was used to reduce indication bias in assessing the relation between LDA and outcomes. 12,13 The PS can be defined as a patient's probability of receiving LDA conditional on his or her individual observed covariates.…”
mentioning
confidence: 99%
“…Postmenstrual age at NICU discharge will be documented, as poorer behavioural outcomes are associated with longer length of hospital stay 118 .…”
Section: Perinatal Data Collectionmentioning
confidence: 99%